A Prognostic Gene-Expression Signature and Risk Score for Meningioma Recurrence After Resection. Issue 1 (29th August 2020) - Chen, William C; Vasudevan, Harish N; Choudhury, Abrar; Pekmezci, Melike; Lucas, Calixto-Hope G; Phillips, Joanna; Magill, Stephen T; Susko, Matthew S; Braunstein, Steve E; Oberheim Bush, Nancy Ann; Boreta, Lauren; Nakamura, Jean L; et al.
Abstract: BACKGROUND: Prognostic markers for meningioma are needed to risk-stratify patients and guide postoperative surveillance and adjuvant therapy. OBJECTIVE: To identify a prognostic gene signature for meningioma recurrence and mortality after resection using targeted gene-expression analysis. METHODS: Targeted gene-expression analysis was used to interrogate a discovery cohort of 96 meningiomas and an independent validation cohort of 56 meningiomas with comprehensive clinical follow-up data from separate institutions. Bioinformatic analysis was used to identify prognostic genes and generate a gene-signature risk score between 0 and 1 for local recurrence. RESULTS: We identified a 36-gene signature of meningioma recurrence after resection that achieved an area under the curve of 0.86 in identifying tumors at risk for adverse clinical outcomes. The gene-signature risk score compared favorably to World Health Organization (WHO) grade in stratifying cases by local freedom from recurrence (LFFR, P < .001 vs .09, log-rank test), shorter time to failure (TTF, F-test, P < .0001), and overall survival (OS, P < .0001 vs .07) and was independently associated with worse LFFR (relative risk [RR] 1.56, 95% CI 1.30-1.90) and OS (RR 1.32, 95% CI 1.07-1.64), after adjusting for clinical covariates. When tested on an independent validation cohort, the gene-signature risk score remained associated with shorter TTF (F-test, P  = .002), compared favorably to WHO grade in stratifying cases by OS ( P  = .003 vs P  = .10), and was significantly associated with worse OS (RR 1.86, 95% CI 1.19-2.88) on multivariate analysis. CONCLUSION: The prognostic meningioma gene-expression signature and risk score presented may be useful for identifying patients at risk for recurrence.